(untitled) (Research, Society and Development, 2022)
Violence against women often happens within the family and the main forms practiced are physical violence, psychological violence, sexual violence, property violence and moral violence. Thus, given the scarce approach to this theme in undergraduate courses, health professionals, especially physicians, face difficulties in acting in situations of violence. Thus, the objective of this work is to discuss the importance of communication in the health sector for the reception of women victims of violence in Brazil. The results showed that the epidemiological profile of violence committed against women in the period from 2009 to 2021, the State of Pará notified a total of 55,490 cases of domestic, sexual and/or other violence against women to SINAN. On average, approximately 3,527 cases were reported per year, with 2020 and 2009 being the years that presented, respectively, the highest and lowest case count: 8,640 and 212. The literature on violence against women in the Brazilian scenario shows that this is a multifaceted problem, where there are failures in the notification, allied to failures in the public security system that are intensified by social factors. Therefore, it is worth emphasizing the importance of expanding communication practices among health professionals for the efficient reception of women victims of domestic violence, with a focus on comprehensive and humanized care.